Hadith #3833 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Umar; Jabla bin Sahaym جبلة بن سحيم; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان (Sunan Abi Dawud)
The Prophet (ﷺ) was brought some dates which contained worms. He then mentioned the rest of the tradition to the same effect as the previous (No 3823).
Grade: Sahih